Never have i ever ebook Never have i ever. - Shepard, Sara (The Lying Game, 2011)
New York Times bestselling series The second book in the New York Times bestselling series The Lying Game, by author of the bestselling Pretty Little Liars series, Sara Shepard. Sutton Mercer is dead, but only a few people know it. Her long-lost twin, Emma, has stepped into her shoes—doing her best to flirt with Sutton's boyfriend, hang with her friends, and live with her family all while tracking down Sutton's murderer. But the killer wants Emma to keep playing the part of Sutton—after all, no missing person means no investigation—and will do anything to make sure Emma toes the line...or else. Perfect for fans of Sara Shepard's #1 New York Times bestselling series Pretty Little Liars, The Lying Game has all the juicy plot lines, to-die-for lifestyles, and compelling secrets that fans love.